Arabino mycolates from synthetic mycolic acids. Issue 22 (2nd June 2016) - Mohammed, Mohsin O.; Baird, Mark S.; Al Dulayymi, Juma'a R.; Jones, Alison; Gwenin, Christopher D.
Abstract: The synthesis of single mono-arabino mycolates, important lipid antigens from mycobacteria is described, using structurally defined synthetic mycolic acids. Preliminary assays indicate that these are differentially antigenic to antibodies in the serum of people with active tuberculosis. Graphical abstract: